Quantum Dots: Applications in Biology - Fontes, Adriana.; Fontes, Adriana.; Santos, Beate Saegesser.; Santos, Beate Saegesser. (Methods in Molecular Biology,, 2014)
In Quantum Dots: Applications in Biology, Second Edition, expert researchers in the field detail consolidated approaches as well as new trends in the field. Organized into five parts, the first part comprises an introduction on Quantum Dots(QDs) as fluorescent probes in Life Sciences. While the second section covers important features about QDs´ preparative processes and characterizations for their successful application as fluorophores. The third part presents main aspects related to QDs methods applied to live cells and tissues. The fourth section focuses on QDs experiments in small animals, and the fifth part demonstrates the versatility of QDs in a set of FRET applications. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Thorough and intuitive, In Quantum Dots: Applications in Biology, Second Edition aids scientists in continuing to study QDs by providing information about methods and protocols helping to expand their research.